SARS-CoV-2 Infects Endothelial Cells In Vivo and In Vitro - Liu, Fengming; Han, Kun; Blair, Robert; Kenst, Kornelia; Qin, Zhongnan; Upcin, Berin; Wörsdörfer, Philipp; Midkiff, Cecily C.; Mudd, Joseph; Belyaeva, Elizaveta; Milligan, Nicholas S.; Rorison, Tyler D.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Objective:SARS-CoV-2 infection can cause fatal inflammatory lung pathology. In addition to the lung, cytokine storm-induced inflammatory cascade also affects other organs. SARS-CoV-2 infection-related vascular inflammation is characterized by endotheliopathy in lung and other organs. Whether SARS-CoV-2 causes endotheliopathy by directly infecting endothelial cells is not known and is the focus of the present study. Approach and Results:We observed 1) the co-localization of SARS-CoV-2 with the endothelial cell marker CD31 in the lungs of SARS-CoV-2-infected mice expressing hACE2 in the lung by intranasal delivery of adenovirus 5-hACE2 (Ad5-hACE2 mice) and non-human primates at both protein and RNA levels, and 2) SARS-CoV-2 proteins in endothelial cells by immunogold labeling and electron microscopic analysis. We also detected the co-localization of SARS-CoV-2 with CD31 in autopsied lung tissue from patients who died from severe COVID-19. Comparative analysis of RNA-sequencing data of the lungs of infected Ad5-hACE2 and Ad5-empty mice revealed upregulated KRAS signaling pathway, a well-known pathway for cellular activation and dysfunction. Further, we showed that SARS-CoV-2 directly infects mature mouse aortic endothelial cells (AoECs) that were activated by performing an aortic sprouting assay prior to exposure to SARS-CoV-2. This was demonstrated by co-localization of SARS-CoV-2 and CD34 by immunostaining and detection of viral particles in electron microscopic studies. Moreover, the activated AoECs became positive for ACE-2 but not quiescent AoECs. Conclusion:our results indicate that in addition to pneumocytes, SARS-CoV-2 also directly infects mature vascular endothelial cells in vivo and ex vivo, which may contribute to cardiovascular complications in SARS-CoV-2 infection, including multipleorgan failure.